MO331LINEAGE TRACING OF REGENERATING PROXIMAL TUBULE CELLS (STC) BY SINGLE CELL PROFILING IN ACUTE KIDNEY INJURY. (29th May 2021) - Stamellou, Eleni; Cheng, Mingbo; Sterzer, Viktor; Leuchtle, Katja; Strieder, Thiago; Boor, Peter; Floege, Jürgen; Costa, Ivan G; Möller, Marcus Johannes
Abstract: Background and Aims: Acute tubular injury accounts for the most common intrinsic cause for acute kidney injury (AKI). The scattered tubular cell (STC) phenotype was discovered as a uniform reaction of tubule cells triggered by injury. Our group was the first to identify an inducible transgenic mouse (PEC-rtTA-mouse) specifically labeling STCs with eGFP. Analysis of the transcriptional factors and associated signaling pathways might reveal the function and role of STCs in AKI. Method: Here, we performed single-cell RNA sequencing of unilateral ischemia-reperfusion murine model of AKI 8, 24, 48 hours and 6 and 12 days after AKI induction. Results: Genes expressing proximal tubular proteins and transporters were markedly downregulated during transition into the STC phenotype upon injury; but expression recovered over time and upon resolution and tubular cells re-differentiated into proximal tubule cells. This provides evidence for the first time that the STC phenotype is a transient and reversible phenotype triggered by injury. Among cells in the STC phenotype, we could identify 2 sub-clusters; a highly proliferating sub-cluster that in the cell cycle analysis showed the highest proportion of cycling cells. The second eGFP-positive cluster appeared very early after AKI and expressed a distinct set of genes (defined by 7 anchor genes). Some of the highly up-regulated genes are known markers of STCs hence confirming the specificity of our transgenic mouse line. Conclusion: Our study provides gene expression patterns specifically in STCs upon injury and repair at multiple time points and suggests that the STC phenotype is a transient and reversible phenotype triggered by injury.